EKSISTENSI MORAL DALAM PENDIDIKAN - Yuniastuti Yuniastuti (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2010)
Abstract: this article mendeskrikan purpose and existence of moral education in educational efforts. For that we need to look back on the goal of education is creating a moral person, independent, mature and mature, honest, noble, virtuous noble character, behave politely, shameless and arrogant and not concerned with the interests of the nation rather than only concemed with personal or group interests.How to create a moral education that is the changes to the measure of success for teachers and students in teaching-leaming process should not only fixated on numbers alone, but more than that, the moral improvement for educators and officials to be role of a model for learners